Comparative Analysis Of Employee Engagement In Employees Generation X, Y, And Z - Muhammad Qoes Atieq (IAIN Syekh Nurjati Cirebon, 2019)
A good organization is an organization that is able to increase employee engagement, in various innovative ways so that employees feel valued and appreciated. Employee engagement in this study refers to an explanation from Schaufeli (2002), which is a motivational condition of employees related to work, which is shown by vigor, dedication, and absorption. Every employee has a different level of engagement, including every employee of various generations. The purpose of this study is to find out and explain the comparison of employee engagement in employees of generation X, Y, and Z. This type of research is a comparative descriptive study with a quantitative approach. Retrieving data using questionnaires distributed online. The sample used by 170 people from various generations of respondents was obtained, namely generation X as much as 32, generation Y as many as 98, and while generation Z as many as 40. While in the data analysis using descriptive analysis, inferential analysis, and one way ANOVA to compare. The results showed that there was a significant difference in the level of employee engagement for employees of generation X, Y, and Z. Employee engagement between generations X and Y were not significantly different, while generation Z was significantly different from generation X and Y.Keywords : employee engagement, generation X, generation Y, dan generation Z.